Membrane Hyperpolarization Is Not Required for Sustained Muscarinic Agonist-Induced Increases in Intracellular Ca(2+) in Arteriolar Endothelial Cells - COHEN, KENNETH D. (2005)
OBJECTIVE: Hyperpolarization modulates Ca(2+) influx during agonist stimulation in many endothelial cells, but the effects of hyperpolarization on Ca(2+) influx in freshly isolated arteriolar endothelial cells are unknown. Therefore, the purpose of the present study was to characterize agonist-induced Ca(2+) transients in freshly isolated arteriolar endothelial cells and to test the hypothesis that membrane hyperpolarization augments agonist-induced Ca(2+) influx into these cells. METHODS: Arterioles were removed from hamster cremaster muscles and arteriolar endothelial cells were enzymatically isolated. Endothelial cells were loaded with Fura 2-AM and the Fura 2 ratio measured photometrically as an index of intracellular Ca(2+). The cells were then stimulated with the muscarinic, cholinergic agonist, methacholine, and the resulting Ca(2+) transients were measured. RESULTS: Methacholine (1 μM) increased the endothelial cell Fura 2 ratio from a baseline of 0.81 ± 0.02 to an initial peak of 1.17 ± 0.05 (n = 17) followed by a sustained plateau of 1.12 ± 0.07. The plateau phase of the Ca(2+) transient was inhibited by removal of extracellular Ca(2+) (n = 12, p < .05), or the nonselective cation channel blockers Gd(3+) (30 μM; n = 7, p < .05) or La(3+) (50 μM; n = 7, p < .05) without significant effect on the baseline or peak (p > .05). The initial peak of methacholine-induced Ca(2+) transients was inhibited by the IP(3)-receptor antagonist xestospongin D (10 μM, n = 5, p < .05). The methacholine-induced Ca(2+) transients were accompanied by endothelial cell hyperpolarization of approximately 14–18 mV, as assessed by experiments using the potentiometric dye, di-8-ANEPPS as well as by patch-clamp experiments. However, inhibition of hyperpolarization by blockade of Ca(2+)-activated K(+) channels with charybdotoxin (100 nM) and apamin (100 nM) (n = 5), or exposure of endothelial cells to 80 or 145 mM KCl (both n = 7) had no effect on the plateau phase of methacholine-induced Ca(2+) transients (p > .05). CONCLUSIONS: Freshly isolated arteriolar endothelial cells display agonist-induced Ca(2+) transients. For the muscarinic agonist, methacholine, these Ca(2+) transients result from release of Ca(2+) from intracellular stores through IP(3) receptors, followed by sustained influx of extracellular Ca(2+). While these changes in intracellular Ca(2+) are associated with endothelial cell hyperpolarization, the methacholine-induced, sustained increase in intracellular Ca(2+) appears to be independent from this change in membrane potential. These data suggest that arteriolar endothelial cells may possess a novel Ca(2+) influx pathway, or that the relationship between intracellular Ca(2+) and Ca(2+) influx is more complex than that observed in other endothelial cells.